'I don't think there is any moral basis for taking money away from people': using discursive psychology to explore the complexity of talk about tax. Issue 1 (1st January 2019) - Carr, Philippa; Goodman, Simon; Jowett, Adam
ABSTRACT: The increasing recognition of the negative impact of income inequality has highlighted the importance of taxation which can function as a redistributive mechanism. Previous critical social psychological research found that talk about restricting the welfare state, that is funded through tax, is formed of ideology that supports the maintenance of income inequality. Therefore, this research explores how speakers use talk about tax to justify income inequality during a UK BBC radio discussion, 'Moral Maze: The moral purpose of tax' which involved public figures discussing the role of tax. This programme was analysed from a critical discursive psychological perspective. It was found that two contrasting constructions of tax were presented: tax as a collective responsibility or tax as an individual burden, whereby speakers drew on social justice and individualistic ideology respectively. Arguments for high tax rates are problematic due to the acceptability of inequality in a meritocracy. By presenting wealthy individuals as more deserving than the less affluent, arguments for higher tax come to be challenged.